2010
DOI: 10.1007/s12311-010-0171-z
|View full text |Cite
|
Sign up to set email alerts
|

Working Memory and Verbal Fluency Deficits Following Cerebellar Lesions: Relation to Interindividual Differences in Patient Variables

Abstract: Findings concerning cognitive impairment in patients with focal cerebellar lesions tend to be inconsistent and usually reflect a mild deficit. Patient variables such as lesion age and the age at lesion onset might affect functional reorganization and contribute to the variability of the findings. To assess this issue, 14 patients with focal vascular cerebellar lesions and 14 matched healthy control subjects performed a verbal working memory and a verbal long-term memory task as well as verbal fluency tasks. Pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 63 publications
(35 citation statements)
references
References 47 publications
(65 reference statements)
2
33
0
Order By: Relevance
“…Despite conflicting results with regard to the laterality and specificity of cerebellar involvement in verbal fluency, clinical and neurophysiological studies have reported that the ability to generate lists of words per the phonemic rule is more affected than under the semantic rule [132, 133, 135, 136, 138, 139], with a specific damage on category switching [138] [132]. …”
Section: Cerebellum and Verbal Fluency (Phonological And Semantic) (Mmentioning
confidence: 99%
“…Despite conflicting results with regard to the laterality and specificity of cerebellar involvement in verbal fluency, clinical and neurophysiological studies have reported that the ability to generate lists of words per the phonemic rule is more affected than under the semantic rule [132, 133, 135, 136, 138, 139], with a specific damage on category switching [138] [132]. …”
Section: Cerebellum and Verbal Fluency (Phonological And Semantic) (Mmentioning
confidence: 99%
“…In the last two decades, many studies have progressively demonstrated the range of cognitive deficits associated with cerebellar dysfunction, including linguistic processing (Klein, Milner, Zatorre, Meyer, & Evans, 1995), verbal fluency (Richter et al, 2005;Peterburs, Bellebaum, Koch, Schwarz, & Daum, 2010), visuospatial functions (Molinari, Petrosini, Misciagna, & Leggio, 2004;Neau, Arroyo-Anllo, Bonnaud, Ingrand, & Gil, 2000), procedural learning (Shin and Ivry, 2003); verbal memory (Grasby et al, 1993), executive functions (Bellebaum and Daum, 2007;Gottwald, Wilde, Mihajlovic, & Mehdorn, 2004), attention (Gottwald, Mihajlovic, Wilde, & Mehdorn, 2003), working memory , sequencing Tedesco et al, 2011), and emotion (Schmahmann & Sherman, 1998;Turner et al, 2007). In a large group of patients with focal cerebellar damage (N ¼ 156), Tedesco et al (2011) found that among the various cognitive domains, the ability to sequence was most severely affected.…”
Section: Introductionmentioning
confidence: 99%
“…Cerebellar contribution to working memory in humans has been established based on human cerebellar lesion and functional imaging studies in healthy subjects [1][2][3][4]. According to the model of Baddeley and Hitch [5], working memory has been subdivided into different components.…”
Section: Introductionmentioning
confidence: 99%